ANTECEDENTS OF MILLENNIALS’ SERVICE USAGE INTENTION: ONLINE GROCERY SERVICE IN INDONESIA - Putri, Alma Roosnelia (ASEAN Marketing Journal, 2021)
Manuscript type: Research Article Research Aims: The research aims to fill in the gap in the existing literature on the usage intention of online grocery shopping in Indonesia. Further, the study intends to examine the influence of perceived usefulness and perceived ease of use to intention to use. Design/methodology/approach: The study was performed on 217 millennial respondents in the are of Jakarta and Greater Jakarta. Further, data results were analyzed using Structural Modelling Equation (SEM), specifically Partial Least Squared method with Smart PLS 3.2.8 software. Research Findings: Further, the research found that enjoyment is the predictor to perceived ease of use; while insignificant to perceived usefulness. E-WOM, perceived web quality and perceived ease of use are key predictors to perceived usefulness; while subjective norm, visibility, perceived risk, and trust are not the influencing factors. E-WOM and perceived web quality are predictors to trust; while trust is not significantly related to perceived usefulness. Moreover perceived ease of use and perceived usefulness to have an influence on the intention to use online grocery service. Theoretical Contribution/Originality: Numerous previous studies had indicated factors of subjective norm, perceived enjoyment, visibility, perceived risk (Driediger and Bhatiasevi, 2019) and trust (Alalwan et. al, 2015) as factors that influence consumers’ acceptance in terms of perceived usefulness and perceived ease of use. In relation with trust, perceived web quality and e-WOM (Al-debei. et. al, 2015) was found to increase the perception of trust that lead to perceived usefulness of online shopping. Practitioner/Policy Implication: Due to differences in the cultural, social, and demographic background of users, results are inapplicable to subjects in other countries. Further, online shopping platforms have various different business models and therefore results cannot be generalized into one. Research limitation/Implications: Explore the ground standard model and characteristics of various online grocery retailers.